Hubungan Pemilih Makanan dan Citra Tubuh dengan Status Gizi pada Remaja Putri SMA Negeri 2 Palu - Alda Asran; Lilik Sofiatus Solikhah; Hardianti Hardianti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Adolescent girls are susceptible to nutritional and psychological problems due to changes during puberty. Selective eating behavior and negative body image perceptions may affect nutritional intake, potentially leading to eating disorders and mental health issues. This study aimed to examine the relationship between food selectivity and body image with nutritional status in adolescent girls. A quantitative, cross-sectional design was used, involving 89 purposively sampled female adolescents aged 15–19 years from a population of 790. Anthropometric measurements were conducted using a microtoise and a digital scale, and data were analyzed using the chi-square test. Results showed that 17.5% of participants were undernourished. There was no significant association between food selectivity and nutritional status (p = 0.454), but a significant association was found between negative body image and abnormal nutritional status (p = 0.001). In conclusion, body image is significantly associated with nutritional status, whereas food selectivity is not, among adolescent girls at SMA Negeri 2 Palu.